Religion in Africa: Experience & Expression - Thomson, Dennis L.; van Beek, Walter E. A. (Heinemann, 1994)
This is the first major collection for over a decade on the subject of African religion. It is part of a continuous stock-taking solidly grounded in archival and field research in Africa and the African diaspora. This book provides the views of some of the most distinguished academics in the context of African history, anthropology, archaeology, politics, comparative religion, health and healing, languages and literatures, and the visual and performing arts.
free